Atlas of Lymph Node Anatomy - Harisinghani, Mukesh G.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2013)
Detailed anatomic drawings and state-of-the-art radiologic images combine to produce this essential Atlas of Lymph Node Anatomy. Utilizing the most recent advances in medical imaging, this book illustrates the nodal drainage stations in the head and neck, chest, and abdomen and pelvis. Also featured are clinical cases depicting drainage pathways for common malignancies. 2-D and 3-D maps offer color-coordinated representations of the lymph nodes in correlation with the anatomic illustrations. This simple, straightforward approach makes this book a perfect daily resource for a wide spectrum of specialties and physicians at all levels who are looking to gain a better understanding of lymph node anatomy and drainage. Edited by Mukesh G. Harisinghani, MD, with chapter contributions from staff members of the Department of Radiology at Massachusetts General Hospital.
Head and Neck Lymph Node Anatomy -- Chest Lymph Node Anatomy -- Abdominal Lymph Node Anatomy -- Pelvic Lymph Node Anatomy -- Pitfalls and Mimics of Lymph Nodes in Imaging.
Keywords: Medicine; Human anatomy; Radiology, Medical; Nuclear medicine; Radiotherapy; Oncology; Medicine & Public Health; Imaging / Radiology; Anatomy; Oncology; Diagnostic Radiology; Radiotherapy; Nuclear Medicine